REVIEW: TONIC POTENCY OF ZINGIBERACEAE FAMILY HERBAL PLANTS IN IMPROVING BODY WELLNESS - Nabilah Azka Nihlah; Imam Adi Wicaksono; Keri Lestari (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Body wellness is closely related to health; it is the ability of a person to perform activities without fatigue. Herbal plants can be used to help improve body health and endurance. The Zingiberaceae family is widely found and used by the Indonesian people. This family is widely used as an ingredient in herbal medicines and seasonings. Herbal plants with the potential to improve body wellness can be seen in their tonic effects. Testing the tonic effect can use several methods, namely, the natatory exhaustion test, hanging test, sleep induction test, and rotarod test in mice. Among these, the natatory exhaustion method is the simplest and can be performed quickly. The method used in preparing this article is to collect and understand the primary literature from online databases, such as Google Scholar. This review article aims to provide scientific information to the public regarding herbal plants from the Zingiberaceae family, which have the potential to help maintain a healthy body. Plants that can be used as health enhancers include Red Ginger, Gajah Ginger, Temu Kunci, Temu Giring, Lempuyang Gajah, and Cardamom. Keywords: Herbal Plant, Zingiberaceae, Tonicum, HealthÂ